(untitled) (Journal of Environmental Microbiology and Toxicology, 2019)
Established approaches for the management of contaminants include things like membrane separation, ion exchange, precipitation, transformation and biosorption. Of all of these technologies, biosorption has lots of features that include low running expenditures, very effective detoxification of toxicants at low levels, low quantity of removal components as well as does not require nutrient needs as with bacterial-based remediation, theaforementioned being restricted to the existence of heavy metals and other toxicants. The biosorption of BDE-3 on spent black tea was successfully fitted to three models—pseudo-1st, pseudo-2nd and Elovich. Statistical analysis based on root-mean-square error (RMSE), adjusted coefficient of determination (adjR2), accuracy factor (AF), bias factor (BF), corrected AICc Bayesian Information Criterion (BIC), (Akaike Information Criterion) and Hannan–Quinn information criterion (HQC) showed that the pseudo-second order model is the best model giving valuable parameters such as the equilibrium sorption capacity qe and the pseudo-second-order rate constant, k2, which can be further utilized in isothermal modelling analysis. Further analysis is needed to provide proof for the chemisorption mechanism usually tied to this kinetic.